An Enhanced VOF Method Coupled with Heat Transfer and Phase Change to Characterise Bubble Detachment in Saturated Pool Boiling - Anastasios Georgoulas; Manolia Andredaki; Marco Marengo (Energies, 2017)
The present numerical investigation identifies quantitative effects of fundamental controlling parameters on the detachment characteristics of isolated bubbles in cases of pool boiling in the nucleate boiling regime. For this purpose, an improved Volume of Fluid (VOF) approach, developed previously in the general framework of OpenFOAM Computational Fluid Dynamics (CFD) Toolbox, is further coupled with heat transfer and phase change. The predictions of the model are quantitatively verified against an existing analytical solution and experimental data in the literature. Following the model validation, four different series of parametric numerical experiments are performed, exploring the effect of the initial thermal boundary layer (ITBL) thickness for the case of saturated pool boiling of R113 as well as the effects of the surface wettability, wall superheat and gravity level for the cases of R113, R22 and R134a refrigerants. It is confirmed that the ITBL is a very important parameter in the bubble growth and detachment process. Furthermore, for all of the examined working fluids the bubble detachment characteristics seem to be significantly affected by the triple-line contact angle (i.e., the wettability of the heated plate) for equilibrium contact angles higher than 45°. As expected, the simulations revealed that the heated wall superheat is very influential on the bubble growth and detachment process. Finally, besides the novelty of the numerical approach, a last finding is the fact that the effect of the gravity level variation in the bubble detachment time and the volume diminishes with the increase of the ambient pressure.